2007
DOI: 10.1080/07373930701291173
|View full text |Cite
|
Sign up to set email alerts
|

Study on Heat Transfer Enhancement of Oscillating-Flow Heat Pipe for Drying

Abstract: The application of oscillating-flow heat pipe (OFHP) in drying is of great potential. In this article, two methods are proposed to enhance the heat transfer of OFHP: (1) pulse heating is adopted instead of conventional continuous heating; and (2) a tube with a nonuniform cross section is introduced. Experiments on the effects of these two methods have been studied in comparison with ordinary OFHP. Experimental results indicate that using the pulse heating and the nonuniform cross section channel can improve th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 14 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…The heat transfer rate is affected by changes in the boundary layer thickness, fluid mixing, and a lowered thermal resistance [16,23]. Several previous studies in engineering design applications have concluded that the presence of an oscillating flow can enhance heat transfer by 15-40% and increase the effective thermal conductivity by 10-60% [16, 21,30,31,53,56]. It has been suggested that this enhancement is mainly due to the fact that oscillations promote fluid mixing and create vortices around the cylinder because the laminar-turbulent transition may be a major mechanism that enhances heat transfer in zero-mean oscillating flow [28,31].…”
Section: Discussionmentioning
confidence: 99%
“…The heat transfer rate is affected by changes in the boundary layer thickness, fluid mixing, and a lowered thermal resistance [16,23]. Several previous studies in engineering design applications have concluded that the presence of an oscillating flow can enhance heat transfer by 15-40% and increase the effective thermal conductivity by 10-60% [16, 21,30,31,53,56]. It has been suggested that this enhancement is mainly due to the fact that oscillations promote fluid mixing and create vortices around the cylinder because the laminar-turbulent transition may be a major mechanism that enhances heat transfer in zero-mean oscillating flow [28,31].…”
Section: Discussionmentioning
confidence: 99%
“…The experimental data obtained will make it possible to develop specialized drying equipment that provides optimal modes and conditions that maximize the drying process. Also, based on the results of the research, the requirements for sources of acoustic impact will be determined and existing ultrasonic emitters will be developed and/or modified to form the required distribution of oscillations in a gaseous medium [10].…”
Section: Introductionmentioning
confidence: 99%